Co-Doped Zn1−xCdxS nanocrystals from metal–organic framework precursors: porous microstructure and efficient photocatalytic hydrogen evolution. Issue 32 (20th July 2017) - Tang, Xiu; Zhao, Jia-Hui; Li, Yu-Han; Zhou, Zi-Ji; Li, Kui; Liu, Fu-Tian; Lan, Ya-Qian
Abstract : Nanoporous Co-doped Zn1− x Cd x S fabricated with ZnCo-ZIFs as templates afford a high H2 -production rate, corresponding to 45.2 and 422.2 times larger than those of Zn0.5 Cd0.5 S and CdS without using ZIF as template. Abstract : Nanoporous Co-doped Zn1− x Cd x S were facilely fabricated via adopting ZIFs as templates, and Cd(NO3 )2 and thiourea as precursors. The highly porous microstructure and uniform Co-doping of the photocatalyst afford a high H2 -production rate (45.2 and 422.2 times larger than those of Zn0.5 Cd0.5 S and CdS), providing an effective way for the development of high performance nanoporous photocatalysts.